Strategy for Sustainable Tourism Village Development case study of Kampung Lahang, Indonesia - Bambang Hengky Rainanto; Andrew Jason; Abdul Talib Bon; Jonathan van Melle; Cecilia Valentina Srihadi; Bambang Rudyanto (STIE Pariwisata API Yogyakarta, 2023)
The aim of this research on sustainable tourism development is to develop and strive for sustainable tourism in Kampung Lahang, Sukabumi Regency, West Jawa Province, Indonesia. Sustainable tourism needs to be developed in Kampung Lahang because it is a priority sector to encourage economic growth, increase regional foreign exchange, empower the community, absorb the workforce, open up job and business opportunities, as well as introduce community products and create a sustainable tourism destination. This research was conducted in Kampung Lahang, Sukabumi Regency using descriptive research with qualitative methodology. Multiple interviews with relevant informants as primary data sources, while secondary data was obtained from literature related to the research. Data collection through observation and interviews. The findings revealed that the local community initially rejected Kampung Lahang, but through discussion and outreach by the Management, Pokdarwis, and Village Government were able to resolve the problem. The Kampung Lahang Management has attempted and carried out a number of developments, such as improving hospitality, improving and maintaining facilities and infrastructure, as well as absorbing labor from the surrounding community. Aspects that support success include understanding and enthusiasm among residents who want to see their village transformed into a sustainable tourism village.